Simulasi Modifikasi Konfigurasi Jaringan Spindel Menjadi Loop Tertutup Untuk Meningkatkan Keandalan Sistem Distribusi Menggunakan Software ETAP - Eko Nio Rizki (Sekolah Tinggi Teknik PLN, 2021)
Distribution reliability network rely on to any factor such as material quality, maintenance, operational pattern, protection device and also network configuration. In the spindle network the level of network reliability is level 3 (SPLN 52-3, 1983: 5). In order to leveling up the network reliability from level 3 to level 5 (zero down time)[2][3] we need to modify the protection system from overcurrent relay and ground fault relay to line differential relay in each distribution substation. Beside that Load Break Switch in each customer cubicle substation and in the connection substation should replaced by circuit breaker. Spindle network which operated open loop in the connection substation switch to normally close operated, so it can be called as closed loop network. This modification purpose is ther is no down time in case off ground fault or phase to phase sort circuit on the network cable. Before this kind of modification and the setting applied into real network, we make a simulation using an application called ETAP and no missmatch trip from 7 time experiment consist of ground fault and phase to phase short circuit in 7 cable